Combination of Synovial Fluid IL-4 and Polymorphonuclear Cell Percentage Improves the Diagnostic Accuracy of Chronic Periprosthetic Joint Infection - Huang, Jiaxing; Wang, Jiawei; Qin, Leilei; Zhu, Bo; Huang, Wei; Hu, Ning (Frontiers in Surgery, 2022)
Abstract Background: Synovial fluid biomarkers have been found to improve the diagnosis of chronic periprosthetic joint infection (PJI); however, no “gold standard” exists yet. Interleukin-4 (IL-4) and polymorphonuclear cell (neutrophil) count in the synovial fluid are crucial in mediating local inflammation during bacterial infections and could be valuable biomarkers for PJI. Methods: This prospective study was conducted to investigate the diagnostic potential of synovial fluid IL-4 (SF-IL4) and polymorphonuclear cell percentage (SF-PMN%) for chronic PJI. A total of 110 patients who underwent revision arthroplasty between January 2019 and October 2020 were enrolled, and 11 patients were excluded. Of 99 patients, 43 were classified as having PJI and 56 as having aseptic failures according to the 2013 Musculoskeletal Infections Society criteria. In all patients, SF-IL4, SF-PMN%, serum C-reactive protein (CRP), and serum erythrocyte sedimentation rate (ESR) were quantified preoperatively. The diagnostic value for each biomarker was analyzed, and optimal cutoff values were calculated. Results: The patient demographics did not significantly vary. The area under the curve of SF-IL4 and SF-PMN% was 0.97 and 0.89, respectively, higher than that for serum ESR (0.72) and serum CRP (0.83). The combination of SF-IL4 and SF-PMN% provided higher specificity (97.0%) and accuracy (96.0%) when the cut-off values were 1.7 pg/mL and 75%, respectively. Conclusion: SF-IL4 is a valuable biomarker for chronic PJI detection, and the combination of SF-IL4 and SF-PMN% improved the diagnostic value of chronic PJI, and further studies are needed until its clinical application.